Penerapan Model Pembelajaran Cooperative Integrated Reading and Composition untuk Meningkatkan Keterampilan Kolaborasi dan Hasil Belajar Siswa pada Pembelajaran Agama Katolik - Monika Handayani Br Ginting; Diah Ayu Suryani Sitanggang; Ermina Waruwu (CV. ALIM'SPUBLISHING, 2026)
This study aims to implement the Cooperative Integrated Reading and Composition (CIRC) learning model to improve collaboration skills and learning outcomes among phase E students in class X-3 at SMA Katolik 2 Kabanjahe in Catholic Religious Education. This research employed Classroom Action Research conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. Data were collected through observation sheets, learning outcome tests, and documentation, then analyzed using descriptive qualitative analysis supported by process and learning achievement indicators. The findings showed that the implementation of the CIRC learning model improved across learning stages, including orientation from 87% to 95%, organization from 90% to 97%, concept introduction from 87% to 92%, publication from 93% to 98%, and reflection and reinforcement from 87% to 98%. Students’ collaboration skills also increased in each indicator, namely working productively from 75% to 88%, actively participating in problem solving from 82% to 88%, maintaining a balance between listening and speaking from 76% to 86%, appreciating group members’ contributions from 73% to 87%, and demonstrating responsibility as group members from 77% to 93%. Learning outcomes also improved, as shown by the increase in the proficient category from 27% to 77%, while the basic and developing categories decreased to 0% in cycle II. These results indicate that CIRC effectively enhances students’ active participation, collaboration, responsibility, and learning achievement. Therefore, CIRC is recommended as an alternative collaborative learning model for Catholic Religious Education, particularly in strengthening cooperative interaction and meaningful understanding of religious learning materials in classroom practice.